Diagnóstico da educação Ambiental nas escolas da microrregião de Capanema - PR: que práxis é esta? - Biral, Raquel Biz (2011)
This research is a study based on the reality of Environment Education accomplished in schools of southeast of Paraná couties: Santa Izabel do Oeste, Realeza, Capanema, Planalto, Pérola do Oeste, Pranchita, Bela Vista da Caroba e Ampére, these counties belong to Núcleo Regional de Educação de Francisco Beltrão. It has been drafted a diagnosis of the practice on the teachers education environment at these schools and how the government has support the teaching work, in a way that is accomplished what is foresaw the PNEA. The participants number were 228. Among them 186 are students and 42 teachers. The students are from the 3rd grade of high school and a group of school for each county. The researches are supported on Gramsci studies. We consider the stimulator potential of Environment education in what it results in the relation school-society. The methodological process in this proposal is guided by the materialistic-historical conception. We have presented some reflections and proposals on Environment Education, through the belief of social transformation. An education based on these proposals is understood as a political journey, committed with an humanizer education from contextualized principles towards the reality. It has been diagnosed that Environment Education is in the schools jusy with some isolated activities in the subjects as Geography and Biology. The Environment Education is among many political, structure, theoretical, social and cultural problems and by the instability caused by the change of government of the state and the country. The excessive schedule of teachers, huge groups of students and the unfair salaries of the teachers, the society moved by consumption of capitalist system also compose the list of problems